ROBLEMS DEVELOPMENT OF ELEMENTARY MATHEMATICAL CONCEPTS IN PRESCHOOL EDUCATION - Kilichova Marhabo Khudoykulovna; Medvedeva Olga Anotolievna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
In this article, the problems of the development of elementary mathematical concepts in preschool education were studied. The formation and development of mathematical concepts in preschool education and educational processes are explained by the opinions of scientists, teachers and psychologists. And recommendations on the pedagogical activity of the educator on the formation and development of mathematical representations in children were given during the organization of training sessions in preschool education.